2011
DOI: 10.1007/s00300-011-1132-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of wintertime eukaryotic community from sea ice and open water in the Baltic Sea, based on sequencing of the 18S rRNA gene

Abstract: The Baltic Sea is one of the world's largest brackish water basins and is traditionally considered to be species poor. Here, we assessed the diversity of the nanosized eukaryotic microbial wintertime community, using molecular ecological methods based on sequencing of small-subunit ribosomal RNA gene clone libraries. The results demonstrate that a rich community of small eukaryotes inhabits the Baltic Sea ice and water during winter. The community was dominated by alveolates and stramenopiles. Ciliates and cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
78
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 61 publications
9
78
0
Order By: Relevance
“…Picoeukaryotes are among the least known protistan groups in the sea ice. The first studies on the diversity of sea-ice protists (not only picoeukaryotes) have shown sea-ice communities to consist of various phylotypes (Eddie et al, 2010;Bachy et al, 2011;Majaneva et al, 2012;Comeau et al, 2013). Our study complements these recent results with the first report on the quantitative distribution of particular groups of picoeukaryotes in first-year sea ice, including percentage of cells actively feeding by phagocytosis.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Picoeukaryotes are among the least known protistan groups in the sea ice. The first studies on the diversity of sea-ice protists (not only picoeukaryotes) have shown sea-ice communities to consist of various phylotypes (Eddie et al, 2010;Bachy et al, 2011;Majaneva et al, 2012;Comeau et al, 2013). Our study complements these recent results with the first report on the quantitative distribution of particular groups of picoeukaryotes in first-year sea ice, including percentage of cells actively feeding by phagocytosis.…”
Section: Discussionsupporting
confidence: 75%
“…The most important are: group coverage by a probe (percentage of sequences within a group that are targeted by the probe), and hits outside a group (Amann and Fuchs, 2008). All but two probes used in our study has coverage 480% (Supplementary Table S1), and all but one (Bolido02) matches all sequences retrieved from sea ice in the previous studies (Majaneva et al, 2012). This indicates that use of CARD-FISH technique enabled reliable estimation of numbers of most of the investigated groups, providing baseline data on the distribution and relative importance of these groups in the sea ice.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations